Are judges influenced by legally irrelevant circumstances?. (22nd July 2020) - Bergius, My; Ernberg, Emelie; Dahlman, Christian; Sarwar, Farhan
Abstract: Judges should not be influenced by legally irrelevant circumstances in their legal decision making and judges generally believe that they manage legally irrelevant circumstances well. The purpose of this experimental study was to investigate whether this self-image is correct. Swedish judges (N = 256) read a vignette depicting a case of libel, where a female student had claimed on her blog that she had been sexually harassed by a named male professor. The professor had sued the student for libel and the student retracted her claim during the hearing. Half of the judges received irrelevant information - that the professor himself had been convicted of libel a year earlier, while the other half did not receive this information. For the outcome variable, the judges were asked to state how much compensation the student should pay the professor. Those judges who received information about the professor himself having been convicted of libel stated that he should be given significantly less compensation than those who did not receive the irrelevant information. The results show that the judges' decision was affected by legally irrelevant circumstances. Implications for research and practice are discussed